2017
DOI: 10.3390/nu9070687
|View full text |Cite
|
Sign up to set email alerts
|

Egg Consumption and Risk of Metabolic Syndrome in Korean Adults: Results from the Health Examinees Study

Abstract: Metabolic syndrome (MetS) is defined as a cluster of metabolic alterations such as abdominal obesity, dyslipidemias, elevated fasting glucose, and hypertension. Studies on the association between egg consumption and MetS are limited and inconsistent. A cross-sectional analysis was conducted to examine the association of egg consumption with MetS among Korean adults aged 40–69 years. A total of 130,420 subjects (43,682 men and 86,738 women) from the Health Examinees Study were selected for the final analysis. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 32 publications
2
52
0
Order By: Relevance
“…Description of the HEXA study rationale, study design, and baseline characteristics can be found in its introductory papers [ 21 , 22 ]. Updated from the previously published HEXA studies, the current study uses the HEXA Gem (HEXA-G) participant sample which includes additional eligibility criteria on the participating sites (i.e., health examination centers and training hospitals) and is outlined in detail in previous literature [ 23 ]. In this study, HEXA-G data from years 2009–2013 were used as prior surveys did not include snoring-related questions.…”
Section: Methodsmentioning
confidence: 99%
“…Description of the HEXA study rationale, study design, and baseline characteristics can be found in its introductory papers [ 21 , 22 ]. Updated from the previously published HEXA studies, the current study uses the HEXA Gem (HEXA-G) participant sample which includes additional eligibility criteria on the participating sites (i.e., health examination centers and training hospitals) and is outlined in detail in previous literature [ 23 ]. In this study, HEXA-G data from years 2009–2013 were used as prior surveys did not include snoring-related questions.…”
Section: Methodsmentioning
confidence: 99%
“…Eggs and their derived products are common foods on the table worldwide (Toralles et al, 2016). Studies have shown that ingesting a certain quantity of eggs per day can promote good health (Dimarco, Norris, Millar, Blesso, & Fernandez, 2017;Shin et al, 2017). Besides dietary consumption, egg ingredients are extensively used in the food industry for antibacterial, culinary, and functional properties (Ren et al, 2020;Silvetti, Morandi, Hintersteiner, & Brasca, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Updated from the previously published HEXA studies [23,24], the current study used the HEXA-G participant sample which includes additional eligibility criteria on the participating sites. Exclusion criteria for the recruiting center are described in a previous study [25]. In the HEXA-G study, 93,306 women were included at baseline.…”
Section: Study Populationmentioning
confidence: 99%